Procoagulant Activity of Endothelial Cells after Infection with Respiratory Viruses - Visseren, F. L. J.; Bouwman, J. J. M.; Bouter, K. P.; Diepersloot, R. J. A.; de Groot, Ph. G.; Erkelens, D. W. (Thrombosis and Haemostasis, 2000)
Influenza virus epidemics are associated with excess mortality due to cardiovascular diseases. There are several case reports of excessive coagulation during generalised influenza virus infection. In this study, we demonstrate the ability of respiratory viruses (influenza A, influenza B, parainfluenza-1, respiratory syncytial virus, adenovirus, cytomegalovirus) to infect lung fibroblasts and human umbilical vein endothelial cells in culture. All viral pathogens induced procoagulant activity in infected endothelial cells, as determined in a one-stage clotting assay, by causing an average 55% reduction in the clotting time. When factor VII deficient plasma was used clotting time was not reduced. The induction of procoagulant activity was associated with a 4- to 5-fold increase in the expression of tissue factor, as measured by the generation of factor Xa. Both experiments indicate that the procoagulant activity of endothelial cells in response to infection with respiratory viruses is caused by upregulation of the extrinsic pathway. Although both enveloped viruses and a non-enveloped virus (adenovirus) induced procoagulant activity in endothelial cells by stimulating tissue factor expression, the role of the viral envelope in the assembly of the prothrombinase complex remains uncertain.We conclude that both enveloped and non-enveloped respiratory viruses are capable of infecting cultured human endothelial cells and causing a shift from anticoagulant to procoagulant activity associated with the induction of tissue factor expression.
Keywords: Endothelium; tissue factor viruses